Prediction of the Number of New Students in the Information Systems Study Program at Adzkia University Using the Monte Carlo Method: Prediksi Jumlah Mahasiswa Baru Program Studi Sistem Informasi Universitas adzkia Menggunakan Metode Monte Carlo - Prima, Wahyu; Eko Syaputra, Aldo; Sapriadi, Sopi; Septi Eirlangga , Yofhanda; Hariani Manurung, Kiki; Hayati, Nova (Journal of Vocational Education and Information Technology (JVEIT), 2024)
This research aims to predict the number of new students in the Information Systems Study Program at Adzkia University using the Monte Carlo method. The Monte Carlo method was chosen because of its ability to handle variability and uncertainty in historical student enrollment data. The data used in this research is data on students who registered from any pathway during the last 3 years. The simulation process is carried out by creating a probabilistic model from historical data and iterating until a prediction distribution is obtained. The research results show that the Monte Carlo method provides fairly accurate estimates of student predictions for the following year, namely (numbers) which can be used for strategic planning for new student admissions in the future. In conclusion, the use of the Monte Carlo method can be an effective tool in predicting the number of new students and assisting universities in making better decisions regarding student admissions.